2016
DOI: 10.3727/096368916x691448
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Human Urine-Derived Stem Cells Transfected with Pigment Epithelium-Derived Factor to Protect Erectile Function in a Rat Model of Cavernous Nerve Injury

Abstract: The aim of this study was to investigate whether intracavernous injection of urine-derived stem cells (USCs) or USCs genetically modified with pigment epithelium-derived factor (PEDF) could protect the erectile function and cavernous structure in a bilateral cavernous nerve injury-induced erectile dysfunction (CNIED) rat model. USCs were cultured from the urine of six healthy male donors. Seventy-five rats were randomly divided into five groups ( n = 15 per group): sham, bilateral cavernous nerve (CN) crush in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 41 publications
2
32
0
Order By: Relevance
“…Reelin (RELN) is a large secreted extracellular matrix glycoprotein that helps regulate processes related to neuronal migration. Pigment epithelium-derived factor (PEDF) displays neurotrophic functions, and a previous study has reported that PEDF could protect against the neurogenic destruction of erectile function [40]. Therefore, these results support our hypothesis that the proteins contained in exosomes could effectively facilitate skeletal muscle and peripheral nerve regeneration by stimulating related signaling pathways.…”
Section: Discussionsupporting
confidence: 78%
“…Reelin (RELN) is a large secreted extracellular matrix glycoprotein that helps regulate processes related to neuronal migration. Pigment epithelium-derived factor (PEDF) displays neurotrophic functions, and a previous study has reported that PEDF could protect against the neurogenic destruction of erectile function [40]. Therefore, these results support our hypothesis that the proteins contained in exosomes could effectively facilitate skeletal muscle and peripheral nerve regeneration by stimulating related signaling pathways.…”
Section: Discussionsupporting
confidence: 78%
“…Various stem cells, such as adipose tissue‐derived stem cells, bone marrow‐derived mesenchymal stem cells, muscle‐derived stem cells, urine‐derived stem cells, have been proved to effectively improve the cavernous nerve (CN) injury‐induced erectile dysfunction (Woo et al ., ; Jeon et al ., ; Martinez‐Salamanca et al ., ; Yang et al ., ). The underlying mechanisms are not still clear now.…”
Section: Discussionmentioning
confidence: 97%
“…While the exact mechanism of action of the stem cells is still debated, two major schools of thought exist , namely a differentiation and a trophic effect. The current most accepted hypothesis involves the release of trophic factors from the cells that produce an environment favourable for local regeneration .…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are most commonly used in the treatment of ED, mainly from three sources: adult, perinatal, and foetal tissues. Adipose‐derived stem cells (ADSCs) , bone marrow‐derived stem cells, urine‐derived stem cells , placental stem cells, umbilical vein endothelial cells (UVECs), and amniotic fluid‐derived stem cells (AFSCs), have shown some level of improvement in ED models. Although each stem cell population has been separately evaluated in various short‐(2 weeks) or middle‐term (4–6 weeks) pre‐clinical in vivo experiments, one important question should be addressed: whether each stem cell population from different sources achieves similar outcomes for the recovery of erectile function in a severe ED model after long‐term follow‐up?…”
Section: Introductionmentioning
confidence: 99%